ζ-crystallin: A Tale of Two Cells - Curthoys, Norman P. (2009)
Initially, ζ-crystallin was identified as the primary protein in rat renal cortical extracts that binds to the AU-rich sequence that mediates the selective stabilization and increased expression of glutaminase mRNA in the renal proximal convoluted tubule during metabolic acidosis. As reported in this issue by Szutkowska, et al. (1), ζ-crystallin also plays an essential role in the stabilization of the Na(+)/K(+)/2Cl(−)-cotransporter mRNA in the medullary thick ascending limb. However, differential effects of siRNA knockdown experiments in the two cells suggest that additional proteins must contribute to the rapid turnover and selective stabilization of the two mRNAs, a process that mediates the renal compensatory response to metabolic acidosis.